Calcium Peroxide Nanoparticles‐Embedded Coatings on Anti‐Inflammatory TiO2 Nanotubes for Bacteria Elimination and Inflammatory Environment Amelioration. Issue 47 (19th October 2021) - He, Ye; Li, Ke; Yang, Xin; Leng, Jin; Xu, Kun; Yuan, Zhang; Lin, Chuanchuan; Tao, Bailong; Li, Xuan; Hu, Jingwei; Dai, Liangliang; Becker, Ryan; et al.
Abstract: Implant‐associated bacterial infections significantly impair the integration between titanium and soft tissues. Traditional antibacterial modifications of titanium implants are able to eliminate bacteria, but the resulting pro‐inflammatory reactions are usually ignored, which still poses potential risks to human bodies. Here, a dual drug‐loading system on titanium has been developed via the adhesion of a catechol motif‐modified methacrylated gelatin hydrogel onto TiO2 nanotubes. Then synthesized CaO2 nanoparticles (NPs) are embedded into the hydrogel, and interleukin‐4 (IL‐4) is loaded into the nanotubes to achieve both antibacterial and anti‐inflammatory properties. The dual drug‐loading system can eliminate Staphylococcus aureus ( S. aureus ) rapidly, attributed to the H2 O2 release from CaO2 NPs. The potential cytotoxicity of CaO2 NPs is also remarkably reduced after being embedded into the hydrogel. More importantly, with the gradual release of IL‐4, the dual drug‐loading system is capable of modulating pro‐inflammatory reactions by inducing M2 phenotype polarization of macrophages. In a subcutaneous infection model, the S. aureus contamination is effectively resolved after 2 days, and the resulting pro‐inflammatory reactions are also inhibited after 7 days. Finally, the damaged tissue is significantly recovered. Taken together, the dual drug‐loading system exhibits great therapeutic potential in effectively killing pathogens and inhibiting the resulting pro‐inflammatory reactions. Abstract : A dual drug‐loading system on titanium implants is developed. The catechol motif‐modified methacrylated gelatin hydrogel encapsulates calcium peroxide nanoparticles and adheres to IL‐4 loaded TiO2 nanotubes. It efficiently eliminates S. aureus contamination and induces M2 phenotype polarization of macrophages both in vitro and in vivo. Moreover, it effectively inhibits pro‐inflammatory response of the infected tissue and improves tissue regeneration.